The Influence of Macroeconomic Variables on Inflation After Inflation Targeting Framework Implementation in Indonesia - Saifullah, Muhammad Ariq (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2023)
The global economic crisis that occurred in 1997, which led to the collapse of the rupiah exchange rate and soaring inflation, made the country realize the importance of economic stability. The problem was then responded by Bank Indonesia by implementing the Inflation Targeting Framework policy. The focus of this study is to observe the inflation condition in Indonesia after the implementation of the Inflation Targeting Framework policy. The purpose of this study is to see the influence of macroeconomic variables such as Gross Domestic Product (GDP), Interest Rates, and Exchange Rates on Inflation in Indonesia. The method used is Vector Error Correction Model (VECM) analysis with the research period from 2005Q4-2021Q4. The results found that GDP and interest rates have a positive effect on inflation. While the Exchange Rate has a negative effect on inflation in Indonesia.